Validating self-made multimedia resources for English teaching and learning in higher education contexts - Sevilla - Pavón, Ana; imeno - Sanz, Ana (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This paper describes the validation of an English language practice and self-assessment online tool developed and implemented at the Universitat Politècnica de València in Spain by researchers of the CAMILLE group. This tool is an integral part of the InGenio FCE Online Course & Tester,designed to support learners intending to take a higher-intermediate proficiency exam. Thetool was submitted to a thorough product evaluation process by 66 learners of English for Specific Purposes. The results obtained are positive in terms of user satisfaction and also shed light on user preferences and possible improvements.